A PHILOSOPHICAL ANALYSIS OF COMPATIBILISM FROM THE INDIGENOUS NOTION OF KAHIMTANG - Arian Gula Acampado (Sanata Dharma University, 2021)
The Freedom-determinism debate is one of the important current discussions. Its scope covers philosophy to theology, psychology, and even the neurosciences and genetics. Though there are already attempts to reconcile the freedom-determinism perspective, a definite answer to it remains unclear. This research attempts to contribute an input offered by an indigenous understanding of the two perspectives. Using the hermeneutic phenomenology on the Visayan people in the Philippines, this paper attempts to contextualize and understand the debate from their perspective. As such freedom and determinism are put into the context of Kahimtang. The discussion is divided in two parts. The first part discusses three themes or nuances of kahimtang: 1) kahimtang as hatag sa Ginoo (God-given), 2) the notion of kahimtang as latid sa kinabuhi (path in life), and 3) the concept of kahimtang as baruganan sa pagkatawo (state of being-human). The second part discusses the determinism and freedom found in the themes of the previous part and argues on a framework of compatibilism in kahimtang. The study concludes that life for the Visayan is an interplay of freedom and determinism.